Macrofungal diversity in small-holder oil palm plantations on tropical peatlands - WIWIK EKYASTUTI; DWI ASTIANI; HANNA ARTUTI EKAMAWANTI; JAMIAT JAMIAT (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ekyastuti W, Astiani D, Ekamawanti HA, Jamiat. 2023. Macrofungal diversity in small-holder oil palm plantations on tropical peatlands. Biodiversitas 24: 3454-3461. Mushrooms play an important role in ecosystems and human life. They can be found in various places including in oil palm plantations. The aim of this study was to survey and identify the population of macroscopic mushrooms or macrofungi in small-holder oil palm plantations on tropical peatlands in Kampung Baru Village, Kubu Raya District, West Kalimantan, Indonesia using the field survey method. In the research area, a dam has been constructed to regulate the water level at 30 cm, 40 cm, 50 cm, and 60 cm from the surface. Sampling was carried out in these four conditions. The study revealed the presence of 34 species of macrofungi belonging to the Basidiomycota. A groundwater level ranging from 40-60 cm from the surface was identified as favorable for macrofungal growth. Meanwhile, a groundwater level of 30 cm from the surface was found to be unsuitable for macrofungal growth in the peatlands. The level of macrofungal species diversity in small-holder oil palm plantations on the peatlands was determined to be moderate.